Evaluatıon Of Facıal Morphology, Muscle Actıvıty And Advantage Of Bıomechanıcal Relatıonshıps In Openbıte - Sevil Akkaya; Nilüfer Darendeliler; Seda Haydar (Galenos Yayinevi, 1997)
In this study 10 cases with skeletal and dental open bite with a chronological age of 10.40±1.12 years were selected as the open bite group. Another 10 cases with skeletal and dental Class I malocclusion with a chronological age of 10.43±1.88 were selected as control. The EMG activities for masseter and anterior temporal mucles of each case were recorded. Selected skeletal parameters were measured on lateral cephalometric films. The moment arm length and mechanical advantage were calculated on the two dimensional models. The moment arm length and the mechanical advantage of masseter in open bite group was found statistically significantly different when compared with control group. In openbite group; a pozitive correlation was found between the mechanical advantage of temporal and SNB and muscle activity level, a negative correlation was found between mechanical advantage of masseter and gonial angle and mandibular plane angle. In the saine group a pozitive correlation was found between the mechanical advantage of both muscles and the muscle activities.